Histopathology status of black tiger shrimp (Penaeus monodon) in the conventional system in Bireuen, Aceh Province - Dedi Fazriansyah Putra; Ulya Khairumi; Iko Imelda Arisa; Elzein Mohammed Fahal (Depik, 2021)
The purpose of this study was to identify the tiger shrimp (Penaeus monodon) histopatology status in traditional cultured ponds at Bireuen Regency, Aceh Province. The sampling was carried out by purposively random method from seven ponds and two shrimps were sampled from each pond. Several water quality parameters were checked like temperature, pH, salinity and ammonia. Result showed that black tiger shrimp (Penaeus monodon) which were cultivated in traditional ponds in the Bireuen Regency, Aceh Province were histopathologically changes. It was suspected the hepatopancreas changes were associated with viral infection like Hepatopancreatica Parvovirus (HPV) and White Feces Disease (WFD). Ammonia concentrations were found higher in some ponds like Alu Buya Village, Jangka Keutapang Village, Jangka Mesjid Village, Alu Kuta Village and Punjot Village. The management of regular feeding and water quality control is highly recommended to anticipate the viral potential attack in traditional shrimp pond farming at Jangka District, Bireuen Regency, Aceh Province.Keywords:Tiger shrimps Histopathology Water quality